Delivering Health and Social Services in English to English-speakers in the Capitale-Nationale Region (CNR) Revised Access Program: 2006-2009 : Translated and Edited Version - Jeffery Hale - Saint Brigid's (JHSB) (2008)
To comply with the latter, the Capitale-Nationale Region's Health and Social Services Network Development Agency (CNR Agency) launched a review of the health and social services offered in English to English speakers in the region.

Executive Summary of the Document "Delivering Health and Social services in English to English-speakers in the Capitale-Nationale Region (CNR) Revised Access Program: 2006-2009" - Jeffery Hale - Saint Brigid's (JHSB) (2008)
Between June and November 2006, the Agency Responsible for Health and Social Services in Québec's Capitale-Nationale region (or the CNR Agency) prepared a comprehensive Access Program report. This document details how health and social services are delivered in English to English speakers in the greater Quebec City region.

Questions and Answers about Access to Health and Social Services in English in the Capitale-Nationale Region (CNR) - Jeffery Hale - Saint Brigid's (JHSB) (2008)

Training and Human Resources Development Project : Annual Report - Dialogue McGill (2008)
The McGill Training and Human Resource Development Project contributes to other Quebec government initiatives aimed at ensuring that English-speaking people in Quebec enjoy equitable access, in their own language, to the full range of health and social services available to the general population. Its two main objectives are to ensure effective communication in English between English-speaking Quebecers and the health and social services workers who serve their needs and to increase the number of English-speaking professionals working in the Quebec health and social services system. The Project involves the implementation of four measures in partnership with stakeholders concerned by the issue of access to health and social services in the English-speaking communities. The 2008-2009 year was an extension of the Project which finished in March 2008.

The Training and Retention of Health Professionals Project - Dialogue McGill (2008)

The Baseline Data Report 2007-2008 : Quebec's Social and Health Survey Information - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2008)
The Health and Social Services Networking and Partnership Initiative (HSSNPI) is a funding program of the Quebec Community Groups Network mandated by Health Canada as a measure of the Federal Action Plan for Official Language Communities. The HSSNPI aims to support the creation of durable links and joint action between English-speaking communities and Quebec’s health and social services system. The Baseline Data Report is a series produced by the Community Health and Social Services Network (CHSSN) to serve as a relevant and comprehensive knowledge base regarding the health status and vitality of Quebec’s English‐speaking population. The report is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders to develop strategies to improve the well‐being of their constituencies.
Parallel title: Compendium of Tables Including Mother Tongue Infromation Derived from 1998 Quebec Social and Health Survey
Keywords: Official Language Minority Community (OLMC)